Pengaruh Pemberian Pupuk Organik Cair (Poc) Urin Kelinci Terhadap Pertumbuhan dan Hasil Caisim (Brassica chinensis L.) - Liz Yanti Andriyani; Baso Daeng; Linda Ernawati Lindongi; Leonardo Hasoloan Malau (Agrotek, 2022)
This study aims to determine the effect of liquid organic fertilizer (LOF) made from rabbit urine on the growth and yield of caisim. This research was conducted using a randomized block design (RAK) consisting of 5 treatments and 6 replications so that 30 experimental units were obtained. The treatments were A0 (control) without LOF, A1 (LOF 30 ml/l water), A2 (LOF 60 ml/l water), A3 (LOF 90 ml/l water), A4 (LOF 120 ml/l water). The results showed that the LOF treatment of rabbit urine at the concentration of 30-120 ml/liter of water gave a significant effect on the components of plant fresh weight and economic fresh weight, while it had no significant effect on the plant growth component. The appliction of LOF rabbit urine with a concentration of 30 ml/liter of water is sufficient enough to get the best fesh weight of caisim.